Private wells in Ireland : a quantitative assessment of groundwater quality, consumer awareness, contamination susceptibility and human health risk - Hynds, Paul (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2012)
A doctoral research study, funded by the Environmental Protection Agency, was undertaken to examine and assess the health risks associated with private groundwater sources in Ireland. Furthermore, the potential contamination pathways and mechanisms, including consumer awareness, were investigated, quantified and modelled, in order to provide risk management and communication tools in the form of a source susceptibility model and guidance for private groundwater consumers in Ireland. Four primary study areas were selected using decision-based criteria for data acquisition and subsequent analyses, with a fifth area used for model verification. Within the four main study areas, 211 private groundwater sources, of differing design and construction characteristics were surveyed using a developed site assessment process. Furthermore, groundwater samples from each assessed source were analysed for a comprehensive suite of physicochemical, chemical and microbial parameters, with a number of these sources tested on a monthly basis for up to 21-months. A groundwater awareness questionnaire was developed and completed with 545 private groundwater users.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin